Measurement and evaluation of some blood components to determine the size of the effect and the rates of development of futsal football players - M. mohammed Hasan (physical education and sport sciences college for women/ Baghdad University, 2022)
The progress in the health aspect is achieved thanks to the practice of sports activities as well as through the use of scientific measurements that belong to the hardware functionality to serve the health aspect The importance of research to make some measurements of some of the components of blood that are related to side career a (white blood cells and red blood platelets as well as the measurement of hemoglobin blood) to assess the 1-2 research problem: After informed researchers on many sources of scientific noticed the lack of scientific research that gives the proportions of evolution in blood components as a result of playing the game of futsal as well as the lack of research on the health aspect of the components of the blood of football players to Eat. So the researchers wanted to measure the proportions of some blood components in order for them to know the amount of scientific precision in the size of the effect happening to these variables as well as give the ratios to the size of their evolution as a result of physical exercise and skill that receives the sample individuals